PENGARUH PAPARAN BAU MENYENGAT PADA DAYA PENCIUMAN DAN TINGKAT OBSTRUKSI NASAL PADA PEKERJA PENGECORAN LOGAM DIKECAMATAN CEPER - Sofyan Raharjo Sugiarto (FKU 16 UMY 101, 2016)
Background: The reduction of quality in human smelling ability can occur due to odorants interference, sensory disorders and neurological disorders. The common causes of smell disorders are nasal obstruction and exposure to toxic substances continuously. In the United States estimated 1.4% suffering smell ability impairment. In Austria, Switzerland and Germany about 80,000 people annually to the ENT with complaints of smell disorders. Objective: To determine the effect of pungent smell exposure toward sense of smell and nasal obstruction level in metal foundry workers in the Ceper district. Methods: This study was conducted cross sectional, 23 metal foundry workers as a test group and 23 Ceper districts resident as a control group. The analysis is a bivariate analysis using chi square test. Data collection is done by giving six kinds of smell to the test group and the control to determine whether there is interference smell. whereas to determine the nasal obstruction, data retrieval is done using a steel plate that has been modified to measure the extent of steam exhalation. Results: From test group obtained 23 people suffer decreased sense of smell, while the control group gained 19 of the 23 people. From Chi Square test, the P score is 0,054. On nasal obstruction examination, there is no nasal obstruction abnormalities from both the test group and the control group.